An analysis on Teacher Talk using Flanders Interaction Analysis Categories (FIAC) - Feny Martina; Ira Rahmadani Utari; Syamsul Riza (International Journal of Innovation and Education Research, 2021)
The problem of this research was some lecturers only used one categories of teacher talks.  The aims of this study were to identify the characteristics and the categories of teacher talk in the classroom using Flanders Interaction Analysis Categories System (FIACS). This study was case study design and qualitative method. The subject of this study was one novice and senior lecturer at IAIN Bengkulu. It used Flanders Interaction Analysis Categories System (FIACS) to analyze teacher’s talk. The researcher used observation and interview for collecting the data. The result both of novice and senior lecturer showed that the characteristics of teacher is content cross and the most frequent is indirect talk. The percentage of teacher characteristics of novice lecturer was 45% while the percentage of teacher characteristics of senior lecturer was 39%. Novice lecturer used asking question and lecturing as the most frequent in indirect and direct talks. The percentage of asking question and lecturing were 39% and 21.5%. In other sides, senior lecturer used asking question and giving direction as the most frequent in indirect and direct talks. The percentage of asking and giving direction were 27.5% and 18.5%. Nevertheless, the occurred categories happened naturally with the consideration of learning situation that takes place. In addition the analysis of teachers’ talk in the classroom would be beneficial for teachers to plan and conduct enhanced learning situation. It concluded teacher talks of novice and senior lecturer in the classroom using Flanders Interaction Analysis Categories (FIAC).